Nutrition and Immune Function : Frontiers in Nutritional Science, No. 1. - Calder, P. C. (CAB International, 2002)
This text provides a review of the roles of specific nutrients in maintaining the immune response and host protection against infection. It also considers the influence of various factors, such as exercise and ageing, on the interaction between nutrition and immune function.